Formação inicial de professores no curso de Pedagogia e a utilização de Tecnologias de Informação e Comunicação - Sperandio, Paula (2019)
The present study has as main theme the investigation of the initial formation of teachers in Pedagogy courses in two universities in the municipality of Erechim-RS, with regard to the use of Information and Communication Technologies (ICT) for the development of pedagogical practices. The objective which grounds the study is to investigate and identify the forms in which the ICT is inserted in the Pedagogy courses of these universities, taking into account the development of pedagogical practices in Basic Education and the presentation of a proposal to the courses participating in the research, with the suggestion of free educational objects which contribute to the integration of technology use in line with the school curriculum of Basic Education. The methodology is a qualitative study which has as instruments data collection and structured interview, with due analysis of the Pedagogical Projects and the Curricular Grid of the above mentioned courses. The subjects who took part in the interview are last semester Pedagogy course students, the coordinators and the teachers who teach ICT-related curricular components. The organization and data analysis occurs from content categories, obeying to three phases: pre-analysis, exploration of material and treatment of results, inference and interpretation based on theoretical review, based on assumptions of authors such as Pimenta (2012), Libâneo (2015), Scheffer (2017), Candau (2012), Kenski (2012b e a, 2013), Scheffer, Comachio e Cenci (2018), Veiga (2012), among others. From this research, it is possible to diagnosis the utilization of ICT in the initial formation of teachers in the Pedagogy course, both in terms of its guiding documents and in the practices carried out, in order to present the ICT potential to future teachers that will act in Basic Education. Based on the results achieved, it is verified that the analyzed documents superficially approach the use of ICT in the formation of teachers, restricting almost exclusively the menus of the disciplines directly related to them, which is reaffirmed in the speeches of all researched segments regarding the practice. Therefore, from the perspective of contributing to the researched courses, in the glance of possibilities of integrating ICT into the curriculum of Early Childhood Education and Early Years, a proposal to utilize free educational objects that contribute to the stimulus of technology aligned with Basic Education curriculum is proposed, final product of this study.